FACTORS AFFECTING FIRM VALUE WITH THE SOCIAL RESPONSIBILITY OF THE COMPANY AS MODELING VARIABLES IN BANKING COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Sitompul, Putri Lestari (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to examine the effect of firm size, firm age, profitability, the proportion of independent commissioners, institutional ownership, and leverage on firm value with corporate social responsibility (CSR) as a moderating variable. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2011-2017. Sampling uses a purposive sampling method, the sample used is 19 banking companies listed on the IDX. So, the number of observations in this study were 133 observations. The type of data used is secondary data derived from financial statements. The data were analysed using multiple linear regression techniques and moderated regression analysis (MRA) using the SPSS program. The results of this study indicate that the variable firm size, profitability, the proportion of independent commissioners, institutional ownership and leverage simultaneously have a significant effect on firm value. Partially, the proportion of the board of commissioners and institutional ownership has a positive but not significant effect on firm value. Variable firm size and profitability partially have a positive and significant effect on firm value, while leverage variables partially have a negative but not significant effect on firm value. CSR moderates the influence of firm size, profitability, institutional ownership, the proportion of independent commissioners and leverage on firm value.